ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP MINAT MENABUNG PADA PT BANK TABUNGAN NEGARA (PERSERO) TBK. CABANG SEMARANG - Novita Himatul Ulya; Embun Duriany Soemarso; Moch. Abdul Kodir (KEUNIS, 2020)
This research aims to determine the significance of the variables influence the product quality, service quality and trust of the customers saving interest at PT Bank Tabungan Negara (Persero) Tbk. Cabang Semarang. This study uses primary data with questioner and secondary data. The population in this study are all savings customers at PT Bank Tabungan Negara (Persero) Tbk. Cabang Semarang. The sampling technique used was purposive sampling and accidental sampling. The analysis model used in this research is Linear Regression Analysis Model, while the data analysis techniques using the F test, t test, and coefficient of determination (R2). In addition, it also tests the quality of the data in the form of tests validity and reliability, as well as a classical assumption test with normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. Test data indicate that the data is valid and reliable and free from irregularities classical assumptions. The analysis and discussion showed that product quality, service quality and trust simulataniously significant influence customers saving interest at PT Bank Tabungan Negara (Persero) Tbk. Cabang Semarang. Variable service quality and trust partially significant influence customer saving interest, while the variable product quality not significantly influence customer saving interest at PT Bank Tabungan Negara (Persero) Tbk. Cabang Semarang.